The Thracian region and the image of its people in the works of Anton Strashimirov examining Bulgarianness (Colloquia Comparativa Litterarum, 2025)
Anton Strashimirov is one of the first Bulgarian authors who wrote in the field of national psychology as early as the beginning of the 20th century. He published “A Book on Bulgarians” in 1918, and five years later, it reappeared in an expanded new edition as “Our People”. This book set the beginning of a popular discourse known as national psychology, which in Bulgaria subsisted until the late 20th century. The main body of Strashimirov's work dealt with the five principal groups of Bulgarians characterised by their different geographical location and dialects: Shops, Moesian people, Thracian people, Rhodopeans, and Macedonian people. This paper deals with the image of Thracian people (typical features of their life, psychological characteristics, and patterns of behaviour) the way Strashimirov depicted them. Anton Strashimirov's ethno-psychological research possesses beyond doubt great literary merits, but his generalisations are also interesting for exemplifying and proving the popular stereotypes which early 20th century Bulgarian writers resorted to when conceiving and constructing the national consciousness.
Keywords: Anton Strashimirov; national psychology; the Thracian region; regional groups